2017
DOI: 10.1126/sciadv.1700231
|View full text |Cite
|
Sign up to set email alerts
|

Classical strong metal–support interactions between gold nanoparticles and titanium dioxide

Abstract: The classical strong metal–support interaction between TiO2 and IB metals was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
409
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 416 publications
(442 citation statements)
references
References 75 publications
32
409
1
Order By: Relevance
“…Previous reports found that physicochemical interactions generated by these associationsb etween the metal and the support can also influence catalyticp roperties, which have been linked to the strong metal-support interaction (SMSI). [20][21][22][23] Guo et al [24] altered the size regimes of the Ru depositsi nR u/CeO 2 assemblies and uncoveredt he relationship with the SMSI. Shen et al [25] reported that Cu/CeO 2 catalysts are highly active for the low-temperature water-gas shift reaction and revealed that the reaction occurs at the copper/ceria interfacial perimeter due to the SMSI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports found that physicochemical interactions generated by these associationsb etween the metal and the support can also influence catalyticp roperties, which have been linked to the strong metal-support interaction (SMSI). [20][21][22][23] Guo et al [24] altered the size regimes of the Ru depositsi nR u/CeO 2 assemblies and uncoveredt he relationship with the SMSI. Shen et al [25] reported that Cu/CeO 2 catalysts are highly active for the low-temperature water-gas shift reaction and revealed that the reaction occurs at the copper/ceria interfacial perimeter due to the SMSI.…”
Section: Introductionmentioning
confidence: 99%
“…High‐resolution transmission electron microscopy (HRTEM) of the nanoparticles suggest that the lattice spacing is about 0.230 nm, which can be attributed to the (111) plane of Au. Importantly, the Au nanoparticles over all the spinel supports are naked with no encapsulation caused by the classical SMSI . Statistics shows that the average sizes of Au nanocrystals supported on ZnCo 2 O 4 , ZnFe 0.5 Co 1.5 O 4 , ZnFeCoO 4 , ZnFe 1.5 Co 0.5 O 4 , and ZnFe 2 O 4 are 3.0 ± 0.7, 3.0 ± 0.8, 3.1 ± 0.7, 3.2 ± 0.7, and 3.4 ± 0.7 nm, respectively, indicating the negligible influence of the ZnFe x Co 2− x O 4 composition on the size distribution of nano Au.…”
mentioning
confidence: 97%
“…Metal–metal oxide catalysts have been widely recognized as an asset for reinforcing catalytic performances in chemical catalysis reactions . Following the strategy of synergistic interfaces in HER, many nanostructured interfaces have been developed, usually with one component based on an oxidized 3d transition metal as a water dissociation site to adsorb hydroxy groups and another component to adsorb hydrogen atoms and desorb hydrogen molecules .…”
Section: Figurementioning
confidence: 88%
“…[2] Metal-metalo xide catalysts have been widely recognized as an asset for reinforcing catalytic performances in chemical catalysis reactions. [8][9][10][11] Following the strategy of synergistic interfaces in HER, [12] many nanostructured interfacesh ave been developed,u sually with one component based on an oxidized 3d transition metal as aw ater dissociation site to adsorb hydroxy groups and another component to adsorb hydrogen atoms and desorbh ydrogen molecules. [13][14][15] With this in mind, we considered ways to design and synthesize various high-efficiency metal-metal oxide HER catalysts rationally and controllably.V anadium-based oxides are earth-abundant, inexpensive, and versatile in their electronic structures, and may be regarded as apromising candidatefor electrocatalysis promoters.…”
mentioning
confidence: 99%